Shark-diving tourism as a ﬁnancing mechanism for shark conservation strategies in Malaysia - Gabriel M.S. Viann; Mark G. Meekan; Abbie A. Rogers; Marit E. Kragt; James M. Alin; Johanna S. Zimmerhackel (2018)
This study estimated the economic value of the shark-diving industry in Semporna, the most popular diving destination of Malaysia, by surveying the expenditures of diving tourists and dive operators through the region. A willingness-to-pay survey was also used to estimate the potential of the industry as a ﬁnancing mechanism for enforcement and management of a hypothetical Marine Protected Area (MPA) to conserve shark populations. The study showed that in 2012, shark-diving tourism provided direct revenues in excess of USD 9.8 million to the Semporna region. These economic beneﬁts had a ﬂow-on eﬀect, generating more than USD 2 million in direct taxes to the government and USD 1.4 million in salaries to the community. A contingent valuation analysis indicated that implementation of a fee paid by divers could generate over USD 2 million for management and enforcement of the MPA each year. These ﬁndings suggest that shark diving is an important contributor to the economy of the Semporna region that could be used as a mechanism to assist ﬁnancial resourcing for management and conservation strategies.